2021
DOI: 10.1002/mp.14638
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of a calibration phantom for quantitative radiography

Abstract: Objective Dual energy radiography (DER) makes it possible to obtain separate images for soft‐tissue and bony structures (tissue maps) based on the acquisition of two radiographs at different source peak‐kilovoltage values. Current DER studies are based on the weighted subtraction method, which requires either manual tuning or the use of precomputed tables, or on decomposition methods, which make use of a calibration to model soft‐tissue and bone components. In this study, we examined in depth the optimum metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…DE images obtained with this method is similar to the logsubtraction algorithm in terms of contrast and noise characteristics (Sabol et al 2001). A linear decomposition assumes a monoenergetic beam (Li et al 2012), therefore, non-linear decomposition approaches were proposed to account for beam hardening through a calibration process (Brody et al 1981, Cardinal and Fenster 1990, Lee et al 2020, Martinez et al 2021. In particular Martinez et al (2021) described an automatic calibration for material decompression method, avoiding the need for a radiology technician with expert knowledge.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…DE images obtained with this method is similar to the logsubtraction algorithm in terms of contrast and noise characteristics (Sabol et al 2001). A linear decomposition assumes a monoenergetic beam (Li et al 2012), therefore, non-linear decomposition approaches were proposed to account for beam hardening through a calibration process (Brody et al 1981, Cardinal and Fenster 1990, Lee et al 2020, Martinez et al 2021. In particular Martinez et al (2021) described an automatic calibration for material decompression method, avoiding the need for a radiology technician with expert knowledge.…”
Section: Discussionmentioning
confidence: 99%
“…A linear decomposition assumes a monoenergetic beam (Li et al 2012), therefore, non-linear decomposition approaches were proposed to account for beam hardening through a calibration process (Brody et al 1981, Cardinal and Fenster 1990, Lee et al 2020, Martinez et al 2021. In particular Martinez et al (2021) described an automatic calibration for material decompression method, avoiding the need for a radiology technician with expert knowledge. Similarly, the calibration process for the log-subtraction DE algorithm applied in this study and previous studies (Darvish-Molla and Sattarivand 2019, Haytmyradov et al 2020) corrects for beam hardening effects.…”
Section: Discussionmentioning
confidence: 99%
“…A realistic calibration phantom can be made up of PMMA as an equivalent of soft-tissue and aluminum 6082 (AL6082) for bone, as proposed in Martinez et al (2020). While PMMA is a good substitute for soft tissue in terms of beam hardening, AL6082 does not match bone very well in this regard.…”
Section: Tissue Equivalent Materialsmentioning
confidence: 99%
“…(4) (5) where μj imply the linear-attenuation coefficient of the specific material, wf is the weighting factor for suppression of the non-interest tissue in DE image, and wf for bone suppression is defined as follows: (6) The doses delivered to the patient by LE and HE are 0.01 to 0.09 mGy, respectively, and the total doses are 0.1 mGy. Therefore, the dose allocation (ξ, values between 0 and 1) is defined as: (7)…”
Section: Dual-energy X-ray Imagingmentioning
confidence: 99%
“…Jeon et al [5] investigated the image quality of virtual monochromatic images synthesized from DE computed tomography, and found that the DE scan mode with the 100/140 kV protocol achieved a better maximum contrastto-noise ratio (CNR), compared to the 80/140 kV protocol for various materials, except for adipose and brain. We noted that a basis material-decomposition using a calibration phantom had been applied for DE radiography [6].…”
Section: Introductionmentioning
confidence: 99%